Food insecurity in homes of mothers of premature newborns with anthropometric alterations at birth. - MONROY TORRES, Rebeca; CASTILLO CHÁVEZ, Ángela Marcela; VIDALEZ OCÁDIZ, Guadalupe; NAVES SÁNCHEZ, Jaime (Nutrición Clínica y Dietética Hospitalaria, 2020)
Introduction: Preterm newborns are physiologically immature and have special nutritional needs for growing and developing adequately. There are not enough studies that show a relationship between food insecurity in households with premature infants. Objective: To analyze food insecurity in the homes of preterm infants and identify its association with variables like family status and newborn anthropometry (weight, length, and head circumference). Methods: A Cross sectional study was conducte in 45 mothers who were applied the Latin American and Caribbean Household Food Security Scale, with preterm newborns from 30 to 37 weeks of gestation (WG) in a public hospital. Results: A 49% households had food security while 51% had food insecutiry (28.8%, 8.8%, 13.3% had mild, moderate, and severe food insecurity respectively). There were differences between the groups more than 1 day of hospital stay (72% households with food security vs 95% households with food insecurity, p = 0.044). The anthropomethric variables showed significant differences for the weight (p = 0.015), length (p = 0.027) and head circumference (p = 0.002) for the newborns with and without food security. Conclusions: It is not only important to control nutrition during pregnancy, but also food security, especially severe food insecurity that the anthropometric variables of preterm newborns can have an impact.